The Relationship Of Self Care With The Quality Of Life Of Type Ii Diabetes Mellitus Patients At Mitra Medika General Hospital Medan - Riza Purnama (Journal Analytica Islamica, 2022)
Background; Type II diabetes mellitus is often known as diabetes. Type II diabetes mellitus is a metabolic disorder characterized by an increase in blood sugar levels above the normal threshold. Objective; To determine the relationship between self-care and the quality of life of type II diabetes mellitus sufferers at Mitra Medika Medan General Hospital in 2015. Materials and Methods; The research design used in this research uses the Analytical Survey method with a Cross Sectional approach. The population in this study was type II diabetes mellitus sufferers, totaling 129 respondents. The sampling used was purposive sampling, namely taking samples for a purpose by determining certain characteristics that are considered representative of the population. The sampling was done using the Slovin technique, totaling 56 respondents. Results; Based on the results of the analysis using the Chi-Square test, it shows that the significant probability value (Asymp.Sig) of Self Care is 0.003<sig value α 0.05, this proves that there is a relationship between self care and the quality of life of type II diabetes mellitus sufferers at home. Mitra Medika Medan General Hospital 2015. Conclusion; This research shows that statistically there is a relationship between self-care and the quality of life of type II diabetes mellitus sufferers at Mitra Medika Medan General Hospital in 2015. Type II diabetes mellitus sufferers are expected to improve self-care behavior to improve quality of life, at the research site it is recommended to provide education to type II diabetes mellitus patients about the relationship between Self Care and the quality of life of type II diabetes mellitus sufferers.